Pengaruh Service Failure Dan Service Recovery Terhadap Loyalitas Pelanggan Alfamart (Studi Kasus Pada Pelanggan Alfamart, Kelurahan Pademangan Barat, Kecamatan Pademangan, Jakarta Utara) - Syifa Kania Putri; Bertadi Nurseno (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract. This research aims to examine and analyze the influence of service failure and service recovery oncustomer loyalty at Alfamart in the West Pademangan Sub-District, Pademangan District, NorthJakarta. A descriptive quantitative approach was employed using a survey method. Data were collectedthrough questionnaires distributed to 200 respondents and analyzed using SmartPLS version 4. Theresults of the t-test (partial test) show that service failure has a negative and significant effect oncustomer loyalty, with a t-statistic of 2.576 > t-table 1.96 and a p-value of 0.010 < 0.05. Servicerecovery also has a positive and significant effect on customer loyalty, with a t-statistic of 7.853 > t-table1.96 and a p-value of 0.000 < 0.05. This means that 45.1% of the variation in customer loyalty can beexplained by these two variablesKeywords: Service Failure, Service Recovery, Customer Loyality, Alfamart